Regional Economic Outlook, October 2017, Middle East and Central Asia. (Regional Economic Outlook, 2017)
Oil exporters in the Middle East and North Africa, Afghanistan, and Pakistan region (MENAP) are continuing to adjust to lower oil prices, which have dampened growth and contributed to large fiscal and external deficits.